ANALISIS KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Dwi Sawitri, Ni Nengah Devi; Ida Ayu, Widia Laksmi Nyoman; Ni Luh, Anom Pancawati Putu (Waisya : Jurnal Ekonomi Hindu, 2024)
This research aims to find the influence of product quality and price on purchasing decisions at Savana Bale Kebaya. The research method uses quantitative methods. Data collection techniques were carried out by means of documentation, observation, interviews and distributing questionnaires. Sampling using techniques Random Sampling with a sample size of 100 respondents. Data analysis techniques and calculating data use SPSS Version 24. The results of the research show that product quality has a positive and significant effect on purchasing decisions at Savana Bale Kebaya. Price has a positive and significant effect on purchasing decisions at Savana Bale Kebaya. There is a simultaneous influence between product quality and price variables on purchasing decisions at Savana Bale Kebaya. The suggestion in this research is that Savana Bale Kebaya owners pay attention to product quality and set the right price to achieve higher purchasing decisions